A vantagem de falar dialeto: aproveitar as variedades não-padrão para a construção de comunidades multilíngües - Steffen, Joachim (Contingentia, 2008)
For the most part, in linguistic policies, which mainly manifest themselves in educational measures, substandard varieties are at best ignored, if not actively suppressed. This often deprives pupils in immigrant situations and coming from a dialect background not only of their right to speaking their own language but also from the opportunity of aquiring the related standard, benefiting from early bilingual education. Instead, the national language is often used as the only language of instruction and is therefore likely to outdominate any other variety. This paper analyses two immigrant groups on the American continent which both represent diglossic communities in which High German as the High Variety has been lost or replaced by the national language while the related dialect is continuously used for in-group communication. Despite structural similarities in the sociolinguistic makeup of the two speech communities, there have been different approaches towards the teaching of standard German. The paper shows that language attitudes toward the substandard play a decisive role in these approaches. It is argued that instead of seeing the dialect as an obstacle for aquiring the standard variety it ought to be viewed as a suitable starting point to learning High German. Far from being an out-fashioned relic, dialects in immigrant communities should be conceived of as vantage ground for building multilingual societies which include the own vernacular as an element of identity, the related standard as a means of international communication and, of course, the national standard as an instrument of integration.